2009
DOI: 10.1590/s0103-84782009005000118
|View full text |Cite
|
Sign up to set email alerts
|

Época de aplicação de nitrogênio e de início da irrigação na fitotoxicidade causada pela aplicação de imidazolinonas em arroz tolerante

Abstract: O uso de herbicidas do grupo químico das imidazolinonas, em cultivares de arroz tolerantes, pode causar fitotoxicidade inicial nessas cultivares. Práticas integradas de manejo, como época de aplicação de nitrogênio e início da irrigação, podem reduzir a fitotoxicidade, acelerando a recuperação das plantas. Em vista disto, o presente trabalho teve por objetivo avaliar o efeito de épocas de aplicação de nitrogênio em cobertura e início da irrigação, visando a minimizar a fitotoxicidade, no arroz IRGA 422 CL, cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…We suggest that continued management with cover fertilizers can help the plants to recover. Camargo et al (2011) observed recovery of rice plants with high levels of injury by the application of post-emergence herbicides, suggesting that the management of the crop and the addition of nutrients by nitrogenous fertilizers (Golden et al, 2017), as well as the entry of water (Avila et al, 2009), contribute to plant recovery. The estimated drift rates using the phytotoxicity level of the sentinel plants were 14, 13, and 5% of the package insert dose (1,920 g e.a.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that continued management with cover fertilizers can help the plants to recover. Camargo et al (2011) observed recovery of rice plants with high levels of injury by the application of post-emergence herbicides, suggesting that the management of the crop and the addition of nutrients by nitrogenous fertilizers (Golden et al, 2017), as well as the entry of water (Avila et al, 2009), contribute to plant recovery. The estimated drift rates using the phytotoxicity level of the sentinel plants were 14, 13, and 5% of the package insert dose (1,920 g e.a.…”
Section: Resultsmentioning
confidence: 99%
“…A inobservância de significância em resposta às doses de nitrogênio indica para o fato de que a planta de arroz não responde de forma diferente ao nutriente quando exposta à deriva de glyphosate. Cabe destacar que, em situações de campo, produtores utilizam de alterações no manejo do nitrogênio em áreas comerciais para promover a recuperação das plantas após exposição à deriva, situação que pode ser favorável para a recuperação da fitotoxicidade a herbicidas como observado para aqueles pertencentes ao grupo das imidazolinonas (AVILA et al,2009). Tabela 1.…”
Section: Resultsunclassified
“…Imidazolinone-tolerant rice varieties can have the ability to detoxify herbicide molecules of that chemical group and recover from injuries caused by their application, as long as the plants are in optimal conditions for their growth and development (Webster & Masson, 2001). Therefore, the adequate crop management as top-dressing nitrogen fertilization in up to five days after herbicide application in post-emergence, as well as the establishment of irrigation in sequence contributes to the mitigation of the herbicide effects (Avila et al, 2009). In study of Sousa et al (2014), it was observed that the photosynthetic apparatus of the rice variety Puitá INTA CL was injured by the application of the commercial rates of the herbicides imazapyr+imazapic and imazethapyr+imazapic.…”
Section: Resultsmentioning
confidence: 99%